Case report: primary acinar cell carcinoma of the liver treated with multimodality therapy - Jordan, Emmet J.; Basturk, Olca; Shia, Jinru; Klimstra, David S.; Alago, William; D’Angelica, Michael I.; Abou-Alfa, Ghassan K.; O’ Reilly, Eileen M.; Lowery, Maeve A. (Journal of Gastrointestinal Oncology; Vol 8, No 5 (October 19, 2017): Journal of Gastrointestinal Oncology, 2017)
We describe a case of primary acinar cell carcinoma (ACC) originating in the liver in a 54-year-old female, diagnosed following persistent abnormal elevated liver function. Imaging revealed two masses, one dominant lesion in the right hepatic lobe and another in segment IVA. A right hepatectomy was performed to remove the larger lesion, while the mass in segment IVA was unresectable due to its proximity to the left hepatic vein. Immunohistochemical staining showed positivity for trypsin and chymotrypsin. Postoperatively the patient underwent hepatic arterial embolization of the other unresectable lesion followed by FOLFOX chemotherapy. At 20 months from diagnosis the patient is currently under observation with a decreasing necrotic mass and no other disease evident. Based on histology, immunohistochemistry and radiological findings a diagnosis of primary ACC of the liver was made. Genomic assessment of somatic mutations within the patient’s tumor was also performed through next generation sequencing and findings were consistent with an acinar malignancy. This case highlights a rare tumor subtype treated with a combination of therapeutic modalities through a multidisciplinary approach.